The Effect Of Engklek Game Modification On Students' Ability To Understand Gradient Material: An Analysis Of Modifications To The Hopscotch Game On Students' Ability To Understand Gradient Material - Setiawan, Yolanda Aracely; Komarullah, Hafif (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2024)
Mathematics is one of the basic knowledge that has an important role in the means of thinking to develop logical, systematic and critical thinking. In mathematics, it has many connections with abstract ideas which are given symbols that are arranged hierarchically, so learning mathematics takes a long time and requires patience, one of which is understanding gradient material. Gradient or slope is a number that states the degree of slope of a line, the more sloping a line is, the greater the gradient. In general, students experience difficulties in learning gradient material due to several factors. One of the factors that makes it difficult for students to understand gradient material is their low understanding of the material, unable to understand the concept of the material, and lack of practice in working on the questions. In overcoming the difficulties in understanding the gradient material above, teachers need to provide interesting learning methods for students. The existence of learning using a modified engklek game makes it easy for students to understand, not get bored quickly and feel entertained by this learning method. Apart from that, in this engklek game method students can think relatively freely and be more active in communicating. The population of this research is class X MAN 2 Jember 2022 students, totaling 1 class X Science 5